PENGARUH REMUNERASI DEWAN DIREKSI, LEVERAGE DAN EFEKTIVITAS KOMITE AUDIT TERHADAP KUALITAS LABA DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Christin Agustina; Susi Dwi Mulyani (Jurnal Akuntansi Trisakti, 2017)
The purpose of this research is to determine the influence of director remuneration, leverage, and audit committee effectiveness on earnings quality with size of company as moderating variable. The independent variables in this model are director remuneration, leverage, audit committee effectiveness, and size of company. The dependent variable is earnings quality. Dependent variable measured with Quality Earnings Ratio (QER).            Data for this research were obtained by the company's financial statement and annual report and the Indonesia Stock Exchange’s website (BEI). Sample that used in this research are 39 companies listed on the BEI for the period 2013-2017. The sampling technique used was purposive sampling method. This research uses moderating multiple regression analysis. An analytical tool that used to analyze the hypothesis is SPSS 21.The result of this research shows that director remuneration has positive influence on earnings quality. Leverage has positive influence on earnings quality. Audit committee effectiveness has positive influence on earnings quality. The size of company has no influence on earnings quality. The size of company is proven not to strengthen the positive influence of director remuneration, leverage, and audit committee effectiveness on earnings quality.